Specific Premature Groups Have Better Benefits When Treating Apnea With Caffeine Than Aminophylline/Theophylline - Lin, Yi-Chieh; Tan, Yin-Ling; Yen, Ting-An; Chen, Chien-Yi; Tsao, Po-Nien; Chou, Hung-Chieh (Frontiers in Pediatrics, 2022)
Abstract Background: Methylxanthines (caffeine; aminophylline/theophylline) are commonly used for apnea of prematurity (AOP) treatment. We aimed to compare the efficacy and adverse effects of caffeine and aminophylline/theophylline. Methods: A retrospective case–control gestational age-matched study investigates patients born between January 2017 and December 2018, 23–35 weeks gestation with birth weights > 500 g treating AOP with caffeine or aminophylline/theophylline. Results: There were 144 cases (48 in caffeine group and 96 in control group). The median treatment durations were 11 and 17 days in caffeine and control group (p=0.002). When tachycardia is defined as heart rate ≥ 160 bpm, the rates were 8.3% and 34.4% in caffeine and control group (p=0.001). When tachycardia is defined as 10 bpm over baseline heart rate, the rates were 41.7% and 63.5% in caffeine and aminophylline/theophylline group (p=0.01). Stratified by gestational age and sex, significant reductions in tachycardia rates with caffeine than theophylline were limited to male infants and infants born at < 30 weeks gestation. Conclusions: For apnea treatment, caffeine has greater efficacy and fewer tachycardia than aminophylline/theophylline, especially in male infants and infants born at < 30 weeks gestation.